Timothy Pickering papers - Pickering, Timothy, 1745-1829.
Correspondence, including original letters (1778-1828), photocopies of letters (1793-1810), and typewritten transcripts of letters (1798-1822); a quartermaster general certificate (1781); photocopy of a statement (1807) concerning the battle of Lexington in 1775; and bank book (1796-1799) for the account of the secretary of state with the Bank of the United States.
In part, photocopies and typewritten transcripts.
U.S. secretary of state, postmaster general, army officer, and representative and senator from Massachusetts.
Collection material in English.
Keywords: Bank of the United States (1791-1811); United States. -- Department of State; Lexington, Battle of, Lexington, Mass., 1775.; Quartermasters -- United States; Massachusetts -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Personal narratives; United States -- History -- Revolution, 1775-1783 -- Supplies and stores; Army officers; Cabinet officers; Representatives, U.S. Congress -- Massachusetts; Senators, U.S. Congress -- Massachusetts